Lubricating wear-resistant aluminum-plastic composite film with high cold punching depth and preparation method of lubricating wear-resistant aluminum-plastic composite film
By using the composite structure of abrasion -resistant and lubricating coating, co -concentration nylon two -way stretching membrane, adhesive layer, aluminum foil, and modified multi -layer co -squeezing acrylic fluid film, the existing aluminum -plastic film is cold and friction The problem of poor sexuality realizes the depth and abrasion resistance of high cold, meet the needs of power battery packaging and improve the service life of the battery.
Patent Information
- Application Number
- CN202411553485.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-02
- Publication Date
- 2025-01-28
AI Technical Summary
The existing aluminum-plastic film has a small cold-pull depth, poor friction and scratch resistance, and cannot meet the requirements of power battery packaging.
Using high -cold deep lubricating abrasion -resistant aluminum -plastic composite membrane, it is made of compounding of wear -resistant lubricating coating, co -agglomeration nylon two -way stretch film, adhesive layer, aluminum foil, and modified multi -layer co -squeezed polyetrane delay membrane. The excellent stretching and anti -impact of the two -way stretching membrane in the co -agglomeration, the resistance of the aluminum foil, the modified multi -layer co -squeezing the electrolyte corrosion of the electrolyte, and the lubrication and wear resistance of wear -resistant lubrication materials , Improve the coldness and abrasion resistance of the composite membrane.
Achieve high -cold depth, lubrication and abrasion resistance, meet the requirements of large power battery packaging, and improve the service life of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum-plastic composite film and a preparation method thereof, in particular to a high cold-punching deep-lubricating wear-resistant aluminum-plastic composite film and a preparation method thereof. Background Art
[0002] Aluminum-plastic film has excellent barrier properties, puncture resistance, electrolyte corrosion resistance and heat sealing properties, and is an ideal battery packaging material. It is widely used in electric vehicles, electric motorcycles, mobile phones, tablet computers, cameras, 5G base stations, and grid energy storage battery packaging.
[0003] With the rapid development of electric vehicles, the demand for lithium batteries is increasing. The cruising range of electric vehicles is the most important technical indicator for electric vehicle manufacturing, and the cruising range depends on the lightweight of the vehicle and the capacity and life of the power battery. The packaging of the power battery affects the quality and service life of the battery to a certain extent. During the operation of the car, it is inevitable that collisions, bumps, and swings from side to side will occur, requiring the power battery to have the properties of impact resistance, friction resistance, scratch resistance, and electrolyte leakage resistance. Therefore, it is very necessary for the battery shell material to have good impact resistance, friction resistance, scratch resistance, and electrolyte corrosion resistance.
[0004] Foreign countries have nearly 20 years of experience in the development of aluminum-plastic films for power battery packaging. Developed countries such as Europe, Japan, the United States, and South Korea have widely promoted the application of soft-packaged power batteries. The shell materials of existing power batteries in China are mainly aluminum and reinforced PPS composite materials. Aluminum and reinforced PPS composite materials fully meet the use requirements of power batteries, but they are heavy; aluminum-plastic films, as lithium battery packaging materials, have the characteristics of light weight and large design freedom, and are generally favored and valued by the industry. In recent years, my country has paid attention to the development of aluminum-plastic films for power batteries, but there has been no large-scale promotion and application. The main problem is that the cold punching depth of aluminum-plastic films in my country is small, and the friction and scratch resistance are poor, which does not meet the requirements of power battery packaging. Therefore, the development of aluminum-plastic films for power battery packaging with high cold punching depth, friction resistance, and scratch resistance will promote the technological progress of my country's electric vehicle industry.
[0005] CN111616315A discloses a battery packaging material, preparation method and use, which uses BOPA6 film as the outer layer material of the composite film, and the outer surface of the BOPA6 film is coated with silicone, which is used to reduce the friction coefficient of the battery material. However, silicone only has a certain lubricating effect and is not an ideal wear-resistant and scratch-resistant material.
[0006] CN101663774B discloses a battery shell packaging material and a battery shell, wherein the outer layer is a biaxially stretched polyamide film with a thickness of 12 to 50 μm, and the density of the film is 1142 to 1146 kg / m 3The middle layer is 5-50μm aluminum foil, and the inner layer is unstretched PP film, which has good deep drawing and stretching formability. However, since the polyamide film used is BOPA6 film, the impact toughness of ordinary BOPA6 film is poor and its cold punching depth is small. Secondly, the unstretched PP film is a homopolymer PP film. Since PP is a non-polar polymer, its adhesion to aluminum foil is poor. The resulting composite film is not suitable for larger battery packaging.
[0007] CN1193442C discloses an aluminum-plastic composite film for polymer batteries and a manufacturing method thereof, wherein the outer layer is a polyester film or a nylon film, the middle layer is an aluminum foil, and the inner layer is composed of a linear low-density polyethylene and a modified copolymer PP. The outer layer of the composite film is a polyester film, and its impact resistance or elongation cannot meet the requirements of battery packaging. The compatibility of the linear low-density polyethylene and PP is poor, which will cause the inner layer composite film to delaminate, affecting the service life of the composite packaging film.
[0008] In summary, it is urgent to find a high cold punching depth lubricating and wear-resistant aluminum-plastic composite film and its preparation method which has large cold punching depth, good cold punching formability, lubricity and wear resistance, simple process, low cost and is suitable for industrial production. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a high cold punching depth lubricating and wear-resistant aluminum-plastic composite film with large cold punching depth, good cold punching formability, lubricity and wear resistance.
[0010] The technical problem to be further solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a preparation method of a high cold-punching deep lubrication wear-resistant aluminum-plastic composite film with simple process, low cost and suitable for industrial production.
[0011] The technical solution adopted by the present invention to solve its technical problems is as follows: a high cold punching deep lubrication wear-resistant aluminum-plastic composite film, which is mainly composed of a wear-resistant lubricating coating, a copolymer nylon biaxially stretched film, an adhesive layer, an aluminum foil and a modified multi-layer co-extruded polypropylene cast film; the wear-resistant lubricating coating is formed by coating the outer surface of the copolymer nylon biaxially stretched film with a wear-resistant lubricating material; one side of the aluminum foil is bonded to the copolymer nylon biaxially stretched film through an adhesive layer formed by an adhesive solution, and the other side of the aluminum foil is thermally composited with a modified multi-layer co-extruded polypropylene cast film that is simultaneously heated and extruded. The role of the copolymer nylon biaxially stretched film as the outer layer material of the aluminum-plastic film is to give the aluminum-plastic film better heat resistance, gas barrier properties, puncture resistance and wear resistance. The middle layer aluminum foil mainly plays the role of blocking water vapor and skeleton; the inner layer modified multi-layer co-extruded polypropylene cast film (MPP film) mainly plays the role of resisting electrolyte corrosion, ensuring that the packaging film is not cracked or perforated by electrolyte corrosion, causing electrolyte leakage. The wear-resistant lubricating material can improve the wear resistance of the composite film, reduce the wear between the battery and its casing, and thus increase the test life of the battery.
[0012] Preferably, the coating amount of the wear-resistant lubricating material is 5 to 20 g / m 2 (More preferably 10 to 15 g / m 2 If the amount of wear-resistant lubricating material applied is too little, that is, the wear-resistant lubricating coating is too thin, it is difficult to apply uniformly. If the wear-resistant lubricating coating is too thick, the production cost is high. At the same time, due to the large amount of wear-resistant lubricating material used, the drying time is long and the output is small.
[0013] Preferably, the wear-resistant lubricating material is mainly composed of a wear-resistant agent, a solid lubricant and a binder solution, and the mass ratio thereof is 6-20:4-12:20-80 (more preferably 8-14:6-10:20-60). If the amount of the wear-resistant agent is too small, the wear-resistant effect is not obvious. If the amount of the wear-resistant agent is too large, it is not well dispersed in the binder solution, and some small aggregated particles may be formed, which affects the surface finish of the aluminum-plastic composite film. If the amount of the solid lubricant is too small, the lubricating effect is poor. If the amount of the solid lubricant is too large, the precipitation of the lubricant may occur, which affects the surface quality of the aluminum-plastic composite film. If the amount of the binder solution is too small, it cannot be guaranteed that the lubricant and the wear-resistant agent can be completely coated and bonded to the surface of the copolymerized nylon biaxially stretched film, resulting in partial detachment. If the amount of the binder solution is too large, it may cause the lubricating wear-resistant layer to be too thick, increasing the production cost of the aluminum-plastic composite film.
[0014] Preferably, the preparation method of the wear-resistant lubricating material is: in a dissolving kettle, respectively add a binder solution, a wear-resistant agent and a solid lubricant, heat and stir, and cool to room temperature.
[0015] Preferably, the wear-resistant agent comprises nano-SiO 2 、SiC、B 4 C. Al 2 O 3 or ZrO 2 One or more of the following. Nano-SiO 2 It can give the aluminum-plastic composite film surface good smoothness and wear resistance, SiC, B 4 C. Al 2 O 3 and ZrO 2 It has excellent wear resistance. More preferably, the wear-resistant agent is nano-SiO 2 and / or Al 2 O 3 .
[0016] Preferably, the solid lubricant includes silicone resin and / or polytetrafluoroethylene resin, etc. Polytetrafluoroethylene resin (PTFE) has excellent lubrication and wear resistance.
[0017] Preferably, the temperature of the heating and stirring is 40-60°C (more preferably 50-60°C) and the time is 30-60 minutes (more preferably 30-40 minutes). If the heating temperature is too low, the viscosity of the binder liquid may be relatively large, the solid wear-resistant agent may be poorly dispersed, and even aggregated into large-sized particles. If the heating temperature is too high, the liquid viscosity may decrease, which may cause partial precipitation of the solid wear-resistant agent. If the stirring time is too short, the wear-resistant agent is not completely dispersed. If the stirring time is too long, the energy consumption is high.
[0018] Preferably, in the high cold punching deep lubrication wear-resistant aluminum-plastic composite film, the coating amount of the binder solution is 5 to 20 g / m 2 (More preferably 10 to 20 g / m 2 ). The main function of the adhesive is to improve the adhesion between the copolymer nylon biaxially oriented film (BOPA film) and the aluminum foil. Polyamide itself has good adhesion, but the polarity of aluminum foil is relatively small. When the two are directly bonded, the bonding strength still does not meet the requirements of battery packaging. By applying a certain amount of adhesive, the bonding strength between the BOPA film and the aluminum foil can be improved. If the amount of adhesive applied is too little, the coating and bonding will be uneven, resulting in separation in some areas due to insufficient bonding. If the amount of adhesive applied is too much, on the one hand, the cost will increase, and on the other hand, due to the large amount of solvent in the adhesive solution and the long drying process, the solvent may not be completely volatilized, resulting in solvent residue, which will affect the bonding effect.
[0019] Preferably, in the adhesive layer of the high cold punching deep lubrication wear-resistant aluminum-plastic composite film and the wear-resistant lubricating material, the adhesive solution used is mainly made of adhesive and solvent in a mass ratio of 1:1-2 (more preferably 1:1.2-2.0). If the amount of solvent is too little, the dissolution speed is slow, and it may even be partially undissolved, affecting its coating thickness. If the amount of solvent is too much, it will affect the coating drying, and may even cause the solution to not be completely volatilized, thereby affecting the bonding strength.
[0020] Preferably, the binder solution is prepared by adding the binder and the solvent into a dissolving kettle, introducing an inert gas to replace the air in the kettle, heating and stirring to dissolve, and cooling to room temperature.
[0021] Preferably, the binder includes one or more of maleic anhydride / methacrylate copolymer, maleic anhydride / methacrylate glycidyl ether copolymer or polyacrylate, etc. The bonding strength of the binder is in the following order: maleic anhydride / methacrylate glycidyl ether copolymer>maleic anhydride / methacrylate copolymer>polyacrylate. More preferably, the binder is maleic anhydride / methacrylate glycidyl ether copolymer, whose molecular chain contains anhydride and epoxy groups with excellent bonding properties, and contains ether bonds in the molecular weight, which gives the copolymer excellent flexibility and is conducive to providing cold punching performance of the aluminum-plastic composite film.
[0022] Preferably, the solvent includes one or more of cyclohexane, cyclohexanone, n-butyl acetate, isobutyl acetate, isooctyl acetate, etc. In view of the solubility and volatility of the solvent in the binder, more preferably, the solvent is one or more of cyclohexanone, isobutyl acetate, isooctyl acetate, etc.
[0023] Preferably, the inert gas is introduced to replace the air in the kettle for ≥ 2 times.
[0024] Preferably, the inert gas is one or more of nitrogen, argon or helium, etc. The inert gas used in the present invention is a high-purity gas with a purity of ≥99.9%.
[0025] Preferably, in the preparation of the binder solution, the temperature for heating and stirring the solution is 40 to 90°C (more preferably 60 to 80°C), the stirring speed is 30 to 60 rpm (more preferably 40 to 50 rpm), and the time is 1 to 3 hours (more preferably 1 to 2 hours). If the heating temperature is too low, the resin dissolves too slowly; if the heating temperature is too high, the solvent will be vaporized; if the stirring speed is too low, the resin dissolves slowly; if the stirring speed is too fast, the energy consumption is high; if the dissolution time is too short, the solution may not be completely dissolved; if the dissolution time is too long, the binder may turn yellow due to heat.
[0026] Preferably, the thickness of the aluminum foil is 30-50 μm (more preferably 40-45 μm). If the aluminum foil is too thin, the strength of the aluminum-plastic composite film is low, and if the aluminum foil is too thick, the rigidity is high, cold punching is difficult, and the production cost is high.
[0027] Preferably, in the copolymerized nylon biaxially oriented film, the intrinsic viscosity of the copolymerized nylon is 3.5 to 4.0 (more preferably 3.8 to 4.0). If the molecular weight of the resin is low, the tensile strength of the produced copolymerized nylon biaxially oriented film (BOPA film) is low, while when the molecular weight of the resin is too high, the extrusion temperature is high and the production cost of the BOPA film increases.
[0028] Preferably, the tensile strength of the copolymer nylon biaxially stretched film is 70-150MPa (more preferably 90-140MPa), and the elongation is 150-250% (more preferably 160-220%). The tensile strength of the BOPA film is related to the molecular weight of the polyamide resin. The larger the molecular weight of the resin, the higher the tensile strength of the biaxially stretched film. The elongation of the BOPA film is related to the molecular weight composition of the nylon resin. Homopolymer PA6 has a higher crystallinity, a more regular molecular chain arrangement, a small tensile deformation, and a smaller elongation. The molecular chain arrangement of copolymer nylon is irregular, and its deformation during stretching is large, and its elongation is high. At the same time, it is also related to the stretching process. The performance of BOPA film has a direct impact on the cold punching depth of aluminum-plastic composite film. When its tensile strength and elongation are small, the cold punching depth is small. That is, when the cold punching depth is large, the BOPA film will produce cracks or even cracks due to too small deformation. Since the copolymer polyamide in the copolymer nylon BOPA film has good flexibility and high tensile elongation, it can provide a larger deformation during cold punching, so that its cold punching depth is large.
[0029] Preferably, the copolymer nylon biaxially oriented film has a thickness of 20 to 50 μm (more preferably 25 to 35 μm).
[0030] Preferably, the copolymer nylon biaxially stretched film is made of copolymer nylon by melt extrusion and biaxial stretching, and can be prepared by existing technology.
[0031] Preferably, the copolymer nylon includes one or more of PA66 / 6, PA11 / 6, PA12 / 6, PA66 / 56 / 6, PA66 / 1010 / 6, PA66 / 12 / 6, PA66 / 1212 / 6, PA66 / 11 / 6, PA11 / 1010 / 6, PA12 / 1010 / 6 or PA1010 / 1212 / 6. Although nylon 6 biaxially oriented film also has the characteristics required of aluminum-plastic film, its elongation is relatively small. The cold punching depth of the aluminum-plastic composite film prepared by using it as the outer layer material of the aluminum-plastic film is generally below 6 mm, which is only suitable for the packaging of small batteries; while as a packaging material for power batteries, the cold punching depth of the aluminum-plastic composite film is required to be greater than 8 mm. The copolymerized nylon biaxially oriented film used in the present invention introduces long carbon chain structural units into the copolymerized nylon resin macromolecular chain, or by adding comonomers, destroys the orderly arrangement of the PA6 molecular chain, reduces the crystallinity of PA6, increases the amorphous chain segment of the macromolecular chain, and gives the copolymerized nylon excellent softness. Its elongation can be greater than 200%. Using it as the outer layer material of the aluminum-plastic composite film can give the aluminum-plastic composite film excellent cold punching formability. The elongation of the copolymer nylon is in the following order: PA12 / 1010 / 6>PA11 / 1010 / 6>PA1010 / 1212 / 6>PA12 / 6>PA11 / 6>PA66 / 1212 / 6>PA66 / 11 / 6>PA66 / 12 / 6>PA66 / 1010 / 6>PA66 / 56 / 6>PA66 / 6. In terms of performance and cost, it is more preferred that the copolymer nylon is one or more of PA66 / 1010 / 6, PA66 / 11 / 6, PA66 / 12 / 6 or PA66 / 6.
[0032] Preferably, the modified multi-layer co-extruded polypropylene cast film has a tensile strength of 20-40 MPa (more preferably 25-35 MPa), and an elongation of 150-500% (more preferably 200-350%). If the elongation of the MPP film is too small, the composite film will deform too little during cold punching, affecting the cold punching depth and thermal composite strength of the composite film; if the elongation of the MPP film is too large, the rigidity of the composite film is small, resulting in easy deformation of the composite film molded product.
[0033] Preferably, the thickness of the modified multi-layer co-extruded polypropylene cast film is 35-50 μm (more preferably 40-45 μm). If the thickness of the MPP film is too small, the corrosion resistance life of the inner layer of the composite film is short, and the electrolyte easily penetrates into the aluminum foil; if the thickness of the MPP film is too large, the low temperature resistance of the composite film is low, that is, the MPP film is easy to become brittle at low temperatures, resulting in micro cracks in the inner layer of the composite film.
[0034] Preferably, the modified multi-layer co-extruded polypropylene cast film comprises: an inner layer, a middle layer and an outer layer, and the mass ratio is 2-3:4-5:3-4.
[0035] Preferably, the inner layer, i.e., the bonding layer with the aluminum foil, is maleic anhydride grafted polypropylene, and its grafting rate is 0.8-1.5% (more preferably 1.0-1.2%), and the melt index is 3.0-5.0 g / 10 min (more preferably 3.0-4.5 g / 10 min). Maleic anhydride grafted polypropylene is used as the inner layer to bond with the aluminum foil because ordinary polypropylene (PP) is a non-polar polymer, has no adhesion, and cannot be bonded to the aluminum foil. Maleic anhydride grafted polypropylene has good polarity and good adhesion to the aluminum foil under heating, ensuring good adhesion between the MPP film and the aluminum foil. If the grafting rate of the grafted PP is too low, its adhesion is poor. The higher the grafting rate, the better the adhesion, but the higher the melt index. If the melt index is too high, it is not conducive to the control of the co-extrusion process.
[0036] Preferably, the middle layer is copolymerized polypropylene, and the melt index is 2.5-3.5 g / 10 min (more preferably 2.7-3.2 g / 10 min). Copolymerized polypropylene is selected for the middle layer because it has high impact resistance. The use of copolymerized PP can improve the impact resistance and cold punch strength of the aluminum-plastic composite film. The higher the melt index of copolymerized PP, the smaller its molecular weight and the smaller its tensile strength. Therefore, copolymerized PP with a lower melt index is suitable for the requirements of aluminum-plastic composite film. The middle layer of the modified multi-layer co-extruded polypropylene cast film is formed by mixing, heating and melting and extruding one or more copolymerized polypropylenes. One or more copolymerized polypropylenes are selected for blending and extrusion according to the requirements of cold punch depth.
[0037] Preferably, the outer layer is homopolymer polypropylene, and the melt index is 2.5-4.0 g / 10 min (more preferably 2.5-3.5 g / 10 min). Homopolymer polypropylene is selected for the outer layer because homopolymer PP has excellent resistance to electrolyte corrosion or permeability, which can effectively ensure that it will not crack due to electrolyte corrosion and improve the service life of the aluminum-plastic composite film. At the same time, the modified multi-layer co-extruded polypropylene cast film requires that the melt extrusion fluidity of each component is close, which is conducive to the stability of the extrusion film forming process.
[0038] The technical solution adopted by the present invention to further solve the technical problem is as follows: a method for preparing a high cold punching deep lubrication wear-resistant aluminum-plastic composite film, comprising the following steps: (1) Bonding and laminating the copolymer nylon biaxially oriented film with aluminum foil: unwinding the dried aluminum foil, pulling it, continuously coating the adhesive solution on one side of the aluminum foil, pre-drying it, laminating it with the copolymer nylon biaxially oriented film, calendering, drying, and rolling it to obtain a copolymer nylon biaxially oriented film / aluminum foil composite; (2) coating of wear-resistant lubricating material: unwinding the copolymer nylon biaxially stretched film / aluminum foil composite obtained in step (1), pulling it, and continuously coating the outer surface of the copolymer nylon biaxially stretched film with wear-resistant lubricating material, drying it, and winding it to obtain a wear-resistant copolymer nylon biaxially stretched film / aluminum foil composite; (3) Composite of wear-resistant copolymerized nylon biaxially stretched film / aluminum foil and modified multilayer co-extruded polypropylene cast film: unwind the wear-resistant copolymerized nylon biaxially stretched film / aluminum foil composite obtained in step (2), pull it, preheat it, heat-combine the other side of the aluminum foil with the modified multilayer co-extruded polypropylene cast film which is simultaneously heated and extruded, cool and calender it with a guide roller, cool it to room temperature, trim it, and roll it up to obtain a high cold punch deep lubrication wear-resistant aluminum-plastic composite film.
[0039] Preferably, in step (1), the coating amount of the binder solution is 5 to 20 g / m 2 (More preferably 10 to 20 g / m 2 ). If the amount of the adhesive solution applied is too small, the adhesion between the aluminum foil and the copolymer nylon biaxially stretched film is poor. If the amount of the adhesive solution applied is too large, the coating thickness is too large, and the production cost increases.
[0040] Preferably, in step (1), the pre-drying temperature is 100-160°C (more preferably 120-140°C), and the residence time is 2-10 min (more preferably 5-8 min). If the pre-drying temperature is too low, the volatile substances in the binder solution evaporate slowly; if the pre-drying temperature is too high, the binder will be thermally degraded, thereby reducing the bonding strength of the binder; if the pre-drying time is too short, the devolatilization is incomplete; if the pre-drying time is too long, the production efficiency is low.
[0041] Preferably, in step (1), after compounding with the copolymer nylon biaxially oriented film, the drying temperature is 100 to 140°C (more preferably 120 to 140°C), and the residence time is 2 to 10 minutes (more preferably 4 to 8 minutes). If the drying temperature is too low, the curing time of the adhesive is long and the production efficiency is low. If the drying temperature is too high, the adhesive and the copolymer nylon biaxially oriented film will be degraded by heat.
[0042] Preferably, in step (1), the surface of the aluminum foil is cleaned before use: the aluminum foil is unrolled, pulled into an acid solution through a guide roller, acid-washed and soaked, then put into water, washed and soaked, dried, and rolled up.
[0043] Preferably, the mass concentration of the acid solution is 2-5%.
[0044] Preferably, the acid solution is hydrochloric acid solution and / or sulfuric acid solution or the like.
[0045] Preferably, the pickling and soaking temperature is room temperature, and the residence time is 2 to 6 minutes (more preferably 3 to 5 minutes).
[0046] Preferably, the water washing and soaking temperature is room temperature, and the residence time is 3 to 8 minutes (more preferably 3 to 5 minutes).
[0047] Preferably, the drying temperature is 100-140° C. (more preferably 110-130° C.), and the residence time is 2-4 min.
[0048] Preferably, when the aluminum foil is cleaned, the pulling speed of unwinding and pulling and the winding speed of winding are both 4-10 m / min (more preferably 6-8 m / min). If the pulling speed of the aluminum foil is too low, the output will be small, and vice versa.
[0049] Preferably, in step (1), when the copolymer nylon biaxially oriented film is bonded and compounded with the aluminum foil, the unwinding and traction speeds and the winding speeds are both 4 to 8 m / min (more preferably 6 to 8 m / min).
[0050] Preferably, in step (2), the coating amount of the wear-resistant lubricating material is 5 to 20 g / m 2 (More preferably 10 to 15 g / m 2 If the amount of wear-resistant lubricating material applied is too little, that is, the wear-resistant lubricating coating is too thin, it is difficult to apply uniformly. If the wear-resistant lubricating coating is too thick, the production cost is high. At the same time, due to the large amount of wear-resistant lubricating material used, the drying time is long and the output is small.
[0051] Preferably, in step (2), the drying temperature is 100-140°C (more preferably 120-140°C), and the residence time is 5-30 min (more preferably 5-10 min). If the drying temperature is too low, the curing time of the binder in the wear-resistant lubricating material is long and the production efficiency is low. If the drying temperature is too high, the binder in the wear-resistant lubricating material and the copolymerized nylon biaxially stretched film will be degraded by heat.
[0052] Preferably, in step (2), the unwinding and traction speeds and the winding speed of the winding are both 4 to 8 m / min (more preferably 6 to 8 m / min).
[0053] Preferably, in step (3), the wear-resistant copolymerized nylon biaxially oriented film / aluminum foil composite is preheated at a temperature of 100 to 140°C and a residence time of 1 to 3 minutes. During the composite process of the wear-resistant copolymerized nylon biaxially oriented film / aluminum foil composite and the modified multi-layer co-extruded polypropylene cast film, the two can only be bonded together when their temperatures are close. If the temperature is too low, the aluminum foil and the inner layer of the MPP film, i.e., the grafted PP, will not bond well, resulting in partial separation, which will affect the cold punch strength of the aluminum-plastic film; if the temperature is too high, the MPP film may be easily deformed by heat flow, and the thickness of the cast film may be lower than the designed thickness.
[0054] Preferably, in step (3), the draft ratio of the thermal composite is 1.1 to 1.2. The draft ratio is the ratio of the traction speed to the extrusion speed of the extrusion die. The draft speed can be adjusted according to the thickness of the aluminum-plastic composite film to be extruded.
[0055] Preferably, in step (3), the method for heating and extruding the modified multi-layer co-extruded polypropylene cast film is: heating and melting the maleic anhydride grafted polypropylene, copolymerized polypropylene and homopolymerized polypropylene through a screw extruder and extruding them into a composite die head respectively.
[0056] Preferably, the temperature zones for heating and melt extrusion of the maleic anhydride grafted polypropylene are, from the feed port to the extrusion die head, 140-160°C, 170-190°C, 180-200°C, 180-200°C, 160-180°C, and 130-150°C.
[0057] Preferably, the temperature zones of the copolymerized polypropylene during heated melt extrusion are, from the feed port to the extrusion die head, 150-160°C, 160-170°C, 170-180°C, 180-200°C, 180-200°C, and 160-180°C.
[0058] Preferably, the temperature zones for heating and melt extrusion of the homopolypropylene are, from the feed port to the extrusion die head, 150-160°C, 165-170°C, 170-180°C, 170-190°C, 160-180°C, and 140-160°C.
[0059] If the co-extrusion temperature is too low, the PP resin will not be plasticized well, which will affect the uneven thickness of the composite film. If the co-extrusion temperature is too high, on the one hand, it will cause high-temperature degradation of PP, resulting in a decrease in the performance of the composite film. On the other hand, it will cause material extrusion instability, resulting in changes in the thickness of the composite film. If the die temperature is controlled too low, the mutual solubility between the resin layers is poor. If the die temperature is too high, unstable flow will occur.
[0060] Preferably, in step (3), the temperature of the thermal composite is 100 to 160° C. (more preferably 100 to 150° C.). If the thermal composite temperature is too low, the MPP film is not softened and melted, and the adhesion with the aluminum foil is low. If the thermal composite temperature is too high, the MPP film is excessively melted, which may cause the MPP film to be thermally degraded.
[0061] Preferably, in step (3), the three-roll composite guide roller is used for thermal composite, specifically: firstly, the composite is thermally composited through guide rollers 1 and 2, and then through guide rollers 2 and 3, wherein the temperature of guide roller 1 is 110-160°C (more preferably 120-150°C), the temperature of guide roller 2 is 100-140°C (more preferably 110-140°C), and the temperature of guide roller 3 is 100-120°C (more preferably 100-110°C). More preferably, the temperature of guide roller 1 is ≥ the temperature of guide roller 2 ≥ the temperature of guide roller 3. If the temperature of thermal composite of guide roller 1 is too low, the traction stretching is unstable, resulting in uneven thickness of the composite film. At the same time, the adhesion is poor when composited with aluminum foil. If the temperature of thermal composite of guide roller 3 is too high, after bonding with aluminum foil, the MPP film may produce large cooling shrinkage during cooling and calendering, resulting in wrinkles on the surface of the stretched film.
[0062] Preferably, in step (3), the temperature of the guide roller for cooling and calendering is 60-90°C (more preferably 60-80°C). The main function of cooling and calendering is to shape and ensure the stability of the thickness of the aluminum-plastic composite. If the cooling and calendering temperature is too low, the MPP film will cool and harden too fast, and the thickness of the aluminum-plastic composite film will be difficult to adjust. If the temperature is too high, the MPP film will be easily deformed during the calendering process.
[0063] Preferably, in step (3), the product is cooled to room temperature via a conveyor belt.
[0064] Preferably, in step (3), the pulling speed of unwinding, pulling, thermal laminating, cooling and calendering and the winding speed of winding are all 4 to 8 m / min (more preferably 6 to 8 m / min).
[0065] The beneficial effects of the present invention are as follows: (1) The high cold punching depth lubricating wear-resistant aluminum-plastic composite film of the present invention is prepared by compounding a copolymer nylon biaxially stretched film, an intermediate aluminum foil and an inner MPP film. Since the copolymer polyamide biaxially stretched film has excellent stretchability and impact resistance, the cold punching depth can reach more than 8.5 mm, and the maximum cold punching depth is 11.2 mm, which fundamentally improves the cold punching depth of the aluminum-plastic composite film; maleic anhydride grafted PP is used as the bonding layer to improve the bonding between the MPP film and the aluminum foil; the copolymer PP is used as the intermediate layer to give the MPP excellent impact resistance; the homopolymer PP is used as the outer layer to give the MPP film excellent electrolyte corrosion resistance and thermal composite performance; the wear-resistant lubricating material coated on the surface of BOPA improves the scratch resistance, the minimum friction coefficient is only 0.15, the minimum scratch resistance △L value is only 0.10, and it has good lubricity; the high cold punching depth lubricating wear-resistant aluminum-plastic composite film of the present invention has a large cold punching depth, good cold punching formability, lubricity and wear resistance, can fully meet the requirements of large power battery packaging, and improve the service life of the power battery; (2) The method of the present invention has simple process, low cost and is suitable for industrial production. DETAILED DESCRIPTION
[0066] The present invention will be further described below in conjunction with the embodiments.
[0067] The copolymer nylon biaxially stretched films BOPA-1, BOPA-2, and BOPA-3 films used in the embodiments of the present invention and the comparative examples (respectively made of PA66 / 1010 / 6 (intrinsic viscosity of 3.8), PA66 / 11 / 6 (intrinsic viscosity of 3.9), and PA66 / 12 / 6 (intrinsic viscosity of 3.9) by melt extrusion and biaxial stretching) and the nylon 6 biaxially stretched film BOPA6 film were purchased from Xiamen Changsu Group, wherein the tensile strength, elongation, and thickness are: BOPA-1: 100 MPa, 160%, 25 μm, BOPA-2: 120 MPa, 180%, 25 μm, BOPA-3: 135 MPa, 195%, 25 μm, BOPA6: 85 MPa, 38%, 25 μm; the binder maleic anhydride / methacrylate glycidyl ether copolymer used purchased from Jinan Feiyue Chemical Co., Ltd.; the solvent used was purchased from Hunan Petrochemical; the aluminum foil used was purchased from Langfang Shenhuang New Material Technology Co., Ltd., with a thickness of 40 μm; the maleic anhydride grafted polypropylene used was purchased from Ningbo Nengzhiguang New Material Co., Ltd., with a grafting rate of 1.2% and a melt index of 3.5 g / 10 min; the copolymer polypropylene used was purchased from Yanshan Petrochemical, with a grade of K8003 and a melt index of 3.2 g / 10 min; the homopolymer polypropylene used was purchased from Yangzi Petrochemical, with a grade of Z30S and a melt index of 3.5 g / 10 min; the inert gas used in the embodiments of the present invention and the comparative examples is a high-purity gas with a purity of ≥99.9%; the raw materials or chemical reagents used in the embodiments of the present invention and the comparative examples, unless otherwise specified, are obtained through conventional commercial channels; the time parameter under traction involved in the embodiments of the present invention and the comparative examples is the residence time.
[0068] The surface of the aluminum foil is cleaned before use: the aluminum foil is unwound at a pulling speed of 8 m / min, pulled into a hydrochloric acid solution with a mass concentration of 3% through a guide roller, acid-washed and soaked for 4 minutes at room temperature, then put into deionized water, washed and soaked for 4 minutes at room temperature, put into a drying oven, dried for 3 minutes at 120° C., and wound up at a winding speed of 8 m / min to obtain an aluminum foil with a cleaned surface.
[0069] A high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 1 The high cold punching deep lubrication wear-resistant aluminum-plastic composite film is mainly composed of a wear-resistant lubricating coating, a copolymer nylon biaxially stretched film BOPA-1, an adhesive layer, an aluminum foil and a modified multi-layer co-extruded polypropylene cast film; the wear-resistant lubricating coating is formed by coating the outer surface of the copolymer nylon biaxially stretched film BOPA-1 with a wear-resistant lubricating material; one side of the aluminum foil is bonded to the copolymer nylon biaxially stretched film BOPA-1 through an adhesive layer formed by an adhesive solution, and the other side of the aluminum foil is thermally composited with the modified multi-layer co-extruded polypropylene cast film that is simultaneously heated and extruded; The coating amount of the wear-resistant lubricating material is 10 g / m 2 ; The preparation method of the wear-resistant lubricating material is as follows: 30 kg of binder solution, 4 kg of Al 2 O 3 、10kg nano-SiO 2 and 6kg PTFE, heat and stir at 60℃ for 30min, cool to room temperature, and serve; The coating amount of the binder solution is 15g / m 2 ; The preparation method of the binder solution is as follows: 22.5 kg of maleic anhydride / methacrylate glycidyl ether copolymer, 5 kg of cyclohexanone, 5 kg of isobutyl acetate, and 17.5 kg of isooctyl acetate are added to a dissolving kettle, high-purity nitrogen is introduced to replace the air in the kettle twice, and then heated and stirred at 80° C. and a stirring speed of 40 rpm for 2 hours to dissolve, and then cooled to room temperature to obtain the solution; The thickness of the aluminum foil is 40 μm; The thickness of the copolymer nylon biaxially stretched film is 25 μm; The tensile strength of the modified multi-layer co-extruded polypropylene cast film is 25 MPa, and the elongation is 460%; the thickness of the modified multi-layer co-extruded polypropylene cast film is 45 μm; The modified multi-layer co-extruded polypropylene cast film comprises: an inner layer, a middle layer and an outer layer, and the mass ratio thereof is 3:4:3; the inner layer, i.e. the bonding layer with the aluminum foil, is maleic anhydride grafted polypropylene, the middle layer is copolymerized polypropylene, and the outer layer is homopolymerized polypropylene.
[0070] A high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 2 The difference between this embodiment and embodiment 1 is that: the tensile strength of the modified multi-layer co-extruded polypropylene cast film is 26MPa, and the elongation is 480%; the thickness of the modified multi-layer co-extruded polypropylene cast film is 45μm; the modified multi-layer co-extruded polypropylene cast film comprises: an inner layer, an intermediate layer and an outer layer, and the mass ratio is 2.5:4.5:3.0; the inner layer, i.e., the adhesive layer with the aluminum foil, is maleic anhydride grafted polypropylene, the intermediate layer is copolymerized polypropylene, and the outer layer is homopolymerized polypropylene. The rest is the same as embodiment 1.
[0071] A high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 3 The difference between this embodiment and embodiment 1 is that the coating amount of the binder solution is 20 g / m 2 The rest is the same as in Example 1.
[0072] A high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 4 The difference between this embodiment and embodiment 1 is that the coating amount of the wear-resistant lubricating material is 15g / m 2 The rest is the same as in Example 1.
[0073] A high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 5 The difference between this embodiment and embodiment 1 is that the copolymerized nylon biaxially stretched film is BOPA-2. The rest is the same as embodiment 1.
[0074] A high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 6 The difference between this embodiment and embodiment 1 is that the copolymerized nylon biaxially stretched film is BOPA-3. The rest is the same as embodiment 1.
[0075] A method for preparing a high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 1-1 (1) Bonding and laminating copolymer nylon biaxially oriented film with aluminum foil: According to the components of Example 1 of the high cold punching deep lubrication wear-resistant aluminum-plastic composite film, the dried aluminum foil is unwound, pulled, and coated with 15 g / m2 of aluminum foil on one side. 2 Continuously apply the adhesive solution, pre-dry at 130° C. for 5 minutes, and then compound with the copolymer nylon biaxially oriented film BOPA-1, calender, dry at 120° C. for 6 minutes, and roll up to obtain a copolymer nylon biaxially oriented film / aluminum foil composite; the unwinding and pulling speeds and the winding speed of the winding up are both 6 m / min; (2) Coating of wear-resistant lubricating material: According to the components of the high cold punching deep lubricating wear-resistant aluminum-plastic composite film embodiment 1, the copolymerized nylon biaxially stretched film / aluminum foil composite obtained in step (1) is unwound, pulled, and coated with a coating amount of 10 g / m 2 Continuously apply the wear-resistant lubricating material, dry at 130° C. for 5 minutes, and roll up to obtain a wear-resistant copolymer nylon biaxially stretched film / aluminum foil composite; the unwinding and pulling speeds and the winding speed of the winding up are both 6 m / min; (3) Composite of wear-resistant copolymerized nylon biaxially stretched film / aluminum foil and modified multilayer co-extruded polypropylene cast film: According to the components of high cold punching deep lubrication wear-resistant aluminum-plastic composite film embodiment 1, the wear-resistant copolymerized nylon biaxially stretched film / aluminum foil composite obtained in step (2) is unwound and pulled. After preheating the wear-resistant copolymerized nylon biaxially stretched film / aluminum foil composite at 140°C for 2 minutes, the composite is placed between guide rollers 1 and 2 in the three-roll composite guide roller. The other side of the aluminum foil is heated and extruded to be composited with the modified multilayer co-extruded polypropylene cast film. The inner layer of the co-extruded polypropylene cast film is maleic anhydride grafted polypropylene. At a draft ratio of 1.2, it is firstly heat-compounded by guide rollers 1 and 2 in the three-roll composite guide roller, and then heat-compounded by guide rollers 2 and 3, wherein the temperature of guide roller 1 is 150°C, the temperature of guide roller 2 is 130°C, and the temperature of guide roller 3 is 110°C. When the guide roller temperature is 80°C, it is cooled and calendered by guide rollers 4 and 5 for finalization, and then air-cooled to room temperature by conveyor belt, trimmed, and rolled to obtain a high cold punching deep lubrication and wear-resistant aluminum-plastic composite film. The modified multi-layer co-extruded polypropylene cast film is heat-extruded and compounded by extrusion as follows: maleic anhydride grafted polypropylene, copolymerized polypropylene and homopolymerized polypropylene are respectively heated and melt-extruded to a compound die by three screw extruders to obtain the film; the temperature zones of the maleic anhydride grafted polypropylene for heat-melt extrusion are 150°C, 180°C, 190°C, 190°C, 170°C and 140°C from the feed inlet to the extrusion die; the temperature zones of the copolymerized polypropylene for heat-melt extrusion are 160°C, 170°C, 180°C, 190°C, 190°C and 160°C from the feed inlet to the extrusion die; the temperature zones of the homopolymerized polypropylene for heat-melt extrusion are 160°C, 170°C, 180°C, 180°C, 170°C and 150°C from the feed inlet to the extrusion die; The pulling speed of the unwinding, pulling, heat compounding, guide roller cooling, cooling calendering and the winding speed of the winding are all 6m / min.
[0076] A method for preparing a high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 1-2 The difference between this method embodiment and method embodiment 1-1 is that in step (3), the draft ratio is 1.1, the temperature of guide rollers 1 and 2 in the three-roll composite guide roller is 140°C, the temperature of guide roller 3 is 100°C, and the cooling and calendering are performed at a guide roller temperature of 60°C. The rest is the same as method embodiment 1-1.
[0077] A method for preparing a high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 2 The difference between this method embodiment and method embodiment 1-1 is that the components of high cold punching deep lubrication wear-resistant aluminum-plastic composite film embodiment 2 are used for preparation. The rest is the same as method embodiment 1-1.
[0078] A method for preparing a high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 3-1 The difference between this method embodiment and method embodiment 1-1 is that: the components of high cold punching deep lubrication wear-resistant aluminum-plastic composite film embodiment 3 are prepared; in step (1), the coating amount of the binder solution is 20g / m 2 The rest is the same as in Example 1-1.
[0079] A method for preparing a high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 3-2 The difference between this method embodiment and method embodiment 3-1 is that in step (1), after compounding with the copolymerized nylon biaxially oriented film BOPA-1, the drying temperature is 140° C. and the drying time is 8 min. The rest is the same as method embodiment 3-1.
[0080] A method for preparing a high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 4-1 The difference between this method embodiment and method embodiment 1-1 is that: the components of high cold punching deep lubrication wear-resistant aluminum-plastic composite film embodiment 4 are prepared; in step (2), the coating amount of the wear-resistant lubricating material is 15g / m 2 The rest is the same as in Example 1-1.
[0081] A method for preparing a high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 4-2 The difference between this method embodiment and method embodiment 4-1 is that in step (2), the drying temperature is 140° C. and the drying time is 8 minutes. The rest is the same as method embodiment 4-1.
[0082] A method for preparing a high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 5 The difference between this method embodiment and method embodiment 1-1 is that the components of high cold punching deep lubrication wear-resistant aluminum-plastic composite film embodiment 5 are used for preparation. The rest is the same as method embodiment 1-1.
[0083] A method for preparing a high cold punching deep lubrication wear-resistant aluminum-plastic composite film Example 6 The difference between this method embodiment and method embodiment 1-1 is that the high cold punching deep lubrication wear-resistant aluminum-plastic composite film is prepared according to the components of embodiment 6. The rest is the same as method embodiment 1-1.
[0084] Comparative Example 1 The difference between this comparative example and method example 1-1 is that in step (1), the copolymerized nylon biaxially oriented film BOPA-1 is replaced with nylon 6 biaxially oriented film BOPA6. The rest is the same as method example 1-1.
[0085] Comparative Example 2 The difference between Comparative Example 2 and Comparative Example 1 is that step (2) is removed, that is, there is no wear-resistant lubricating coating. The rest is the same as Comparative Example 1.
[0086] Comparative Example 3 The difference between this comparative example and method example 1-1 is that in step (3), the modified multi-layer co-extruded polypropylene cast film is replaced by a co-extruded film of grafted PP and homopolymer PP in a mass ratio of 3:7. The rest is the same as method example 1-1.
[0087] In order to evaluate the performance of the high cold punching depth lubricating and wear-resistant aluminum-plastic composite films of Examples 1 to 6 of the present invention and the aluminum-plastic films of Comparative Examples 1 to 3, tests were performed according to the following testing standards and methods: (1) Cold punching depth: The dimensions of the automatic cold punching forming mold: lower concave film 20×10×(7-10) mm, upper convex film: 18×8×(6.9-9.9) mm, the forming depth was measured, and whether cracks were generated was observed; (2) Friction coefficient testing standard: GB / T1006-1988; (3) Scratch resistance testing standard: GMW14688, the smaller the ΔL value, the better the scratch resistance of the material; the results are shown in Table 1.
[0088] Table 1 Performance comparison of high cold punching deep lubrication wear-resistant aluminum-plastic composite films of Examples 1 to 6 of the present invention and aluminum-plastic films of Comparative Examples 1 to 3
[0089] It can be seen from Table 1 that the average cold punching depth of the high cold punching depth lubricating and wear-resistant aluminum-plastic composite films of Examples 1 to 6 of the present invention is 9.2 mm, without cracks, the minimum cold punching depth is 8.5 mm, and the maximum cold punching depth is 11.2 mm; the average friction coefficient is 0.177, the minimum friction coefficient is only 0.15, and the maximum friction coefficient is 0.19; the average scratch resistance △L value is 0.12, the minimum △L value is only 0.10, and the maximum △L value is only 0.15. In Comparative Example 1, which uses BOPA6 film as the outer layer material of the aluminum-plastic film, the cold punching depth of the aluminum-plastic film is only 5.5mm, which is much smaller than that of the embodiment of the present invention, and has fine cracks, and is only suitable for the packaging of small batteries; Comparative Example 2 is not coated with wear-resistant lubricating material on the basis of Comparative Example 1, and its friction coefficient is as high as 0.29, which is 1.6 times the average friction coefficient of the high cold punching depth lubricating wear-resistant aluminum-plastic composite film of the present invention, and the scratch resistance △L value is as high as 0.4, which is 3.3 times the average scratch resistance △L value of the high cold punching depth lubricating wear-resistant aluminum-plastic composite film of the present invention; the modified multi-layer co-extruded polypropylene cast film in Comparative Example 3 lacks a copolymerized polypropylene layer, resulting in low impact resistance and cold punching strength, and the cold punching depth is only 7.0mm. In summary, it is shown that the high cold punching depth lubricating wear-resistant aluminum-plastic composite films of Examples 1 to 6 of the present invention have excellent cold punching formability and lubrication wear resistance, and are ideal packaging materials for power batteries.
Claims
1. A high cold punching deep lubrication wear-resistant aluminum-plastic composite film, characterized by: It is mainly composed of a wear-resistant lubricating coating, a copolymer nylon biaxially stretched film, an adhesive layer, an aluminum foil and a modified multi-layer co-extruded polypropylene cast film; the wear-resistant lubricating coating is formed by coating the outer surface of the copolymer nylon biaxially stretched film with a wear-resistant lubricating material; one side of the aluminum foil is bonded to the copolymer nylon biaxially stretched film through an adhesive layer formed by an adhesive solution, and the other side of the aluminum foil is thermally composited with the modified multi-layer co-extruded polypropylene cast film that is simultaneously heated and extruded.
2. According to claim 1, the high cold punching deep lubrication wear-resistant aluminum-plastic composite film is characterized by: The coating amount of the wear-resistant lubricating material is 5 to 20 g / m 2 ; The wear-resistant lubricating material is mainly composed of a wear-resistant agent, a solid lubricant and a binder solution, and the mass ratio thereof is 6-20:4-12:20-80; The preparation method of the wear-resistant lubricating material is: in a dissolving kettle, a binder solution, a wear-resistant agent and a solid lubricant are added respectively, heated and stirred, and cooled to room temperature; the wear-resistant agent includes one or more of nano-SiO2, SiC, B4C, Al2O3 or ZrO2; the solid lubricant includes silicone resin and / or polytetrafluoroethylene resin; the heating and stirring temperature is 40-60°C, and the time is 30-60min.
3. The high cold punching deep lubrication wear-resistant aluminum-plastic composite film according to claim 1 or 2, characterized in that: In the high cold punching deep lubrication wear-resistant aluminum-plastic composite film, the coating amount of the adhesive solution is 5 to 20 g / m 2 ; In the bonding layer of the high cold punching deep lubrication wear-resistant aluminum-plastic composite film and the wear-resistant lubricating material, the adhesive solution used is mainly made of an adhesive and a solvent in a mass ratio of 1:1-2; the preparation method of the adhesive solution is: adding the adhesive and the solvent into a dissolving kettle, introducing an inert gas to replace the air in the kettle, heating and stirring to dissolve, cooling to room temperature, and then the adhesive is ready; the adhesive includes one or more of maleic anhydride / methacrylate copolymer, maleic anhydride / methacrylate glycidyl ether copolymer or polyacrylate; the solvent includes one or more of cyclohexane, cyclohexanone, n-butyl acetate, isobutyl acetate or isooctyl acetate; introducing an inert gas to replace the air in the kettle for ≥2 times; the inert gas is one or more of nitrogen, argon or helium; in the preparation of the adhesive solution, the temperature of heating, stirring and dissolving is 40-90°C, the stirring speed is 30-60rpm, and the time is 1-3h.
4. The high cold punching deep lubrication wear-resistant aluminum-plastic composite film according to any one of claims 1 to 3, characterized in that: The thickness of the aluminum foil is 30 to 50 μm; in the copolymer nylon biaxially stretched film, the intrinsic viscosity of the copolymer nylon is 3.5 to 4.0; the tensile strength of the copolymer nylon biaxially stretched film is 70 to 150 MPa, and the elongation is 150 to 250%; the thickness of the copolymer nylon biaxially stretched film is 20 to 50 μm; the copolymer nylon includes one or more of PA66 / 6, PA11 / 6, PA12 / 6, PA66 / 56 / 6, PA66 / 1010 / 6, PA66 / 12 / 6, PA66 / 1212 / 6, PA66 / 11 / 6, PA11 / 1010 / 6, PA12 / 1010 / 6 or PA1010 / 1212 / 6.
5. The high cold punching deep lubrication wear-resistant aluminum-plastic composite film according to any one of claims 1 to 4, characterized in that: The tensile strength of the modified multi-layer co-extruded polypropylene cast film is 20-40 MPa, and the elongation is 150-500%; the thickness of the modified multi-layer co-extruded polypropylene cast film is 35-50 μm; The modified multi-layer co-extruded polypropylene cast film comprises: an inner layer, an intermediate layer and an outer layer, with a mass ratio of 2-3:4-5:3-4; the inner layer, i.e., the bonding layer with the aluminum foil, is maleic anhydride grafted polypropylene, with a grafting rate of 0.8-1.5% and a melt index of 3.0-5.0 g / 10 min; the intermediate layer is copolymerized polypropylene with a melt index of 2.5-3.5 g / 10 min; and the outer layer is homopolymerized polypropylene with a melt index of 2.5-4.0 g / 10 min.
6. A method for preparing a high cold-punching deep lubrication wear-resistant aluminum-plastic composite film as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Bonding and laminating the copolymer nylon biaxially oriented film with aluminum foil: unwinding the dried aluminum foil, pulling it, continuously coating the adhesive solution on one side of the aluminum foil, pre-drying it, laminating it with the copolymer nylon biaxially oriented film, calendering, drying, and rolling it to obtain a copolymer nylon biaxially oriented film / aluminum foil composite; (2) coating of wear-resistant lubricating material: unwinding the copolymer nylon biaxially stretched film / aluminum foil composite obtained in step (1), pulling it, and continuously coating the outer surface of the copolymer nylon biaxially stretched film with wear-resistant lubricating material, drying it, and winding it to obtain a wear-resistant copolymer nylon biaxially stretched film / aluminum foil composite; (3) Composite of wear-resistant copolymerized nylon biaxially stretched film / aluminum foil and modified multilayer co-extruded polypropylene cast film: unwind the wear-resistant copolymerized nylon biaxially stretched film / aluminum foil composite obtained in step (2), pull it, preheat it, heat-combine the other side of the aluminum foil with the modified multilayer co-extruded polypropylene cast film which is simultaneously heated and extruded, cool and calender it with a guide roller, cool it to room temperature, trim it, and roll it up to obtain a high cold punch deep lubrication wear-resistant aluminum-plastic composite film.
7. The method for preparing the high cold-punching deep lubrication wear-resistant aluminum-plastic composite film according to claim 6, characterized in that: In step (1), the coating amount of the binder solution is 5 to 20 g / m 2 ; The pre-drying temperature is 100-160°C, and the residence time is 2-10 min; after being compounded with the copolymer nylon biaxially stretched film, the drying temperature is 100-140°C, and the residence time is 2-10 min; The surface of the aluminum foil is cleaned before use: the aluminum foil is unwound, pulled into the acid solution through a guide roller, acid-washed and soaked, then put into water, washed and soaked, dried, and rolled up; the mass concentration of the acid solution is 2-5%; the acid solution is a hydrochloric acid solution and / or a sulfuric acid solution liquid; the acid pickling and soaking temperature is room temperature, and the residence time is 2 to 6 minutes; the water washing and soaking temperature is room temperature, and the residence time is 3 to 8 minutes; the drying temperature is 100 to 140°C, and the residence time is 2 to 4 minutes; when the aluminum foil is cleaned, the traction speed of unwinding and traction and the winding speed of winding are both 4 to 10 m / min; when the copolymer nylon biaxially stretched film is bonded and compounded with the aluminum foil, the traction speed of unwinding and traction and the winding speed of winding are both 4 to 8 m / min.
8. The method for preparing the high cold-punching deep lubrication wear-resistant aluminum-plastic composite film according to claim 6 or 7, characterized in that: In step (2), the coating amount of the wear-resistant lubricating material is 5 to 20 g / m 2 The drying temperature is 100-140°C, and the residence time is 5-30 min; the unwinding and traction speeds and the winding speeds of the winding are both 4-8 m / min.
9. The method for preparing the high cold-punching deep lubrication wear-resistant aluminum-plastic composite film according to any one of claims 6 to 8, characterized in that: In step (3), the preheating temperature of the wear-resistant copolymerized nylon biaxially stretched film / aluminum foil composite is 100-140°C, and the residence time is 1-3 min; the draft ratio of the thermal composite is 1.1-1.2; the method for heating and extruding the modified multi-layer co-extruded polypropylene cast film is: heating and melting maleic anhydride grafted polypropylene, copolymerized polypropylene and homopolymerized polypropylene are respectively extruded to a composite die by a screw extruder to obtain a composite film; the temperature zone temperature of the heated melt extrusion of the maleic anhydride grafted polypropylene is 140-160°C, 170-190°C, 180-200°C, 180-200°C, 160-180°C, and 130-150°C from the feed inlet to the extrusion die; the temperature zone temperature of the heated melt extrusion of the copolymerized polypropylene is 150-160°C, 160-170°C, 170-180°C, and 180 ~200℃, 180~200℃, 160~180℃; the temperature zone temperature of the homopolymer polypropylene heating melt extrusion, from the feed inlet to the extrusion die head is: 150~160℃, 165~170℃, 170~180℃, 170~190℃, 160~180℃, 140~160℃; the temperature of the thermal compounding is 100~160℃; entering the three-roll composite guide roller for thermal compounding, specifically : firstly perform thermal compounding through guide rollers 1 and 2, and then perform thermal compounding through guide rollers 2 and 3, wherein the temperature of guide roller 1 is 110-160°C, the temperature of guide roller 2 is 100-140°C, and the temperature of guide roller 3 is 100-120°C; the temperature of the guide roller for cooling and calendering is 60-90°C; the film is cooled to room temperature through a conveyor belt; the traction speed of unwinding, traction, thermal compounding, cooling and calendering and the winding speed of winding are all 4-8m / min.
Citation Information
Patent Citations
Packing material for battery case and battery case
CN101663774B
Making process of shredded salted yolk
CN111616315A
Packaging material for polymer cell and method for producing same
CN1193442C
High composite aluminum-plastic membrane for polymer lithium-ion battery
CN105552251A
Lithium battery soft packaging film manufactured by hot-pressing process
CN106207021A